(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
the article mainly describes the problems and prospects of the development of public-private partnerships in the current modern economy and their specific characteristics in economic sectors. The article analyzes the advantages and disadvantages of the mechanism of public-private partnership in the conditions of our country, the opportunities and threats of its introduction, the practice of implementing projects and their features are revealed. Also, directions for the consistent implementation of a number of necessary steps to encourage the use of the public-private partnership mechanism in the near future are scientifically based.